Legal Effectiveness in Handling Covid-19 in Batu Bara Regency North Sumatra Province - Marzuki Marzuki; Indra Janis; Nurasiah Harahap; M. Faisal Rahendra; Dewi Pangestuti; Meri Susanti; Siska Annggreni Lubis (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Covid-19 or “Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-COV-2) become an epidemic for almost all countries in the world, including Indonesia. In Batu Bara Regency, based on the data obtained, there were also 259 confirmed cases, and 119 positive Covid-19 people, 2 cases died and 86 people recovered. Therefore, to overcome the Covid-19 case, Bara Bara Regent Regulation Number 58 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as Efforts to Prevent and Control Corona Virus Disease 2019 in Batu Bara Regency and various implementing regulations, so research is needed to review the effectiveness of the law in handling Covid-19 in Batu Bara Regency. This study uses normative and empirical legal research, with a statute approach, a case approach and a conceptual approach. Based on research data, the level of public knowledge of the regulations issued by Batu Bara Regency Government in tackling Covid-19 is very high, namely from 235 respondents there are 168 (71.49%) who know, while only 67 (28.51%) do not know). Even the respondent's questionnaire data shows the public's desire to give strict sanctions for health protocol violators, namely 200 (85.11%), while only 35 (14.89%) disagree. However, based on research data, respondents indicated that only 35 (14.9%) stated that an action had been taken, while 200 (85.1%) stated that there had been no significant action taken by the Batu Bara Regency Government against violations, which means the effectiveness of the Regent Regulation. Batu Bara Regency No. 58 of 2020 has not fully materialized. Therefore, it still needs strengthening to become a Regional Regulation, and it must be continuously provided with legal socialization to the public, especially those related to the response to Covid-19, so that it can create better legal awareness of the community.